2022
DOI: 10.1515/med-2022-0530
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA ZFAS1 promotes intervertebral disc degeneration by upregulating AAK1

Abstract: We investigated the function of lncRNA zinc finger antisense 1 (ZFAS1) in intervertebral disc degeneration (IDD) progression in vitro and in vivo. Nucleus pulposus (NP) tissues were obtained from 20 patients with IDD. IL-1β was used to stimulate primary NP cells to establish the IDD models in vitro. Gene expression was determined by RT-qPCR. 5-Ethynyl-2′-deoxyuridine and flow cytometry were performed to determine cell proliferation and apoptosis, and western blotting was conducted to measure the apoptosis- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The apoptosis of macrophages was detected with flow cytometry using an Annexin V-FITC/PI Apoptosis Detection Kit (Vazyme Biotech), according to the manufacturer’s instructions but with slight modifications [ 81 ]. Briefly, HD11 and PMA-treated THP-1 macrophages and were incubated with APEC EVs for 24 h. The cells were digested with EDTA-free trypsin.…”
Section: Methodsmentioning
confidence: 99%
“…The apoptosis of macrophages was detected with flow cytometry using an Annexin V-FITC/PI Apoptosis Detection Kit (Vazyme Biotech), according to the manufacturer’s instructions but with slight modifications [ 81 ]. Briefly, HD11 and PMA-treated THP-1 macrophages and were incubated with APEC EVs for 24 h. The cells were digested with EDTA-free trypsin.…”
Section: Methodsmentioning
confidence: 99%
“…This previous study also revealed that ZNFX1 antisense RNA 1 (ZFAS1) was upregulated in degenerative NP tissues and NP cells treated with IL-1β, and that ZFAS1 competitively bound to miR-4711-5p through a ceRNA mechanism, thereby affecting the expression of adaptor-associated kinase 1, which is the target of miR-4711-5p. Silencing ZFAS1 may inhibit IDD progression by reducing NP apoptosis and ECM degradation ( 72 ). Similar to most lncRNAs, long intergenic nonprotein coding RNA 284 was revealed to be upregulated in IDD tissues and IL-1β-induced NP cells, and it activated the Wnt/β-catenin pathway by sponging miR-205-3p, thereby inhibiting NP cell proliferation and ECM synthesis ( 73 ).…”
Section: Research Progress Of Lncrnas In Iddmentioning
confidence: 99%